2023
DOI: 10.3390/hematolrep15040059
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Hematological Complications and Treatment in COVID-19

Armand N. Yazdani,
Arian Abdi,
Prathosh Velpuri
et al.

Abstract: COVID-19, caused by SARS-CoV-2, and its variants have spread rapidly across the globe in the past few years, resulting in millions of deaths worldwide. Hematological diseases and complications associated with COVID-19 severely impact the mortality and morbidity rates of patients; therefore, there is a need for oversight on what pharmaceutical therapies are prescribed to hematologically at-risk patients. Thrombocytopenia, hemoglobinemia, leukopenia, and leukocytosis are all seen at increased rates in patients i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 97 publications
0
2
0
Order By: Relevance
“…Additionally, monoclonal antibody therapies have been authorized for COVID-19 treatment, offering passive immunity, and reducing the risk of severe disease progression [ 49 ]. However, adverse hematological events associated with COVID-19 therapeutics and vaccination have been noted, and must be carefully examined, particularly in patients with hematological malignancies [ 50 , 51 ].…”
Section: Treatment Approaches For H1n1 Influenza and Covid-19mentioning
confidence: 99%
“…Additionally, monoclonal antibody therapies have been authorized for COVID-19 treatment, offering passive immunity, and reducing the risk of severe disease progression [ 49 ]. However, adverse hematological events associated with COVID-19 therapeutics and vaccination have been noted, and must be carefully examined, particularly in patients with hematological malignancies [ 50 , 51 ].…”
Section: Treatment Approaches For H1n1 Influenza and Covid-19mentioning
confidence: 99%
“…As previously reviewed, [10][11][12][13] a large number of studies have reported substantially reduced platelet counts in COVID-19 and the reduction has often been attributed to platelet hyperactivation/hyperaggregability and a presumed resultant shortened platelet lifespan (attributions also supported by animal studies reported by Wong et al 1 ). Lowered platelet count is the most parsimonious explanation for the lower mean serum 5-HT values reported for COVID-19 patients in the studies referenced by Wong et al However, without platelet counts it is not possible to know if other factors (especially 5-HT exposure and uptake inhibition) are playing a role in those previously reported reductions in serum 5-HT.…”
mentioning
confidence: 91%